2015
DOI: 10.1186/s12885-015-1546-9
|View full text |Cite
|
Sign up to set email alerts
|

M1 and M2 macrophages derived from THP-1 cells differentially modulate the response of cancer cells to etoposide

Abstract: BackgroundTumor associated macrophages (TAMs) are present in high density in solid tumors. TAMs share many characteristics with alternatively activated macrophages, also called M2. They have been shown to favor tumor development and a role in chemoresistance has also been suggested. Here, we investigated the effects of M2 in comparison to M1 macrophages on cancer cell sensitivity to etoposide.MethodsWe set up a model of macrophage polarization, starting from THP-1 monocytes differentiated into macrophages usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
614
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 792 publications
(686 citation statements)
references
References 41 publications
31
614
1
3
Order By: Relevance
“…This result was in accordance with several in vitro studies, indicating THP-1-derived macrophages as a well-characterized model for studying macrophage polarization [16,17,2325]. …”
Section: Resultssupporting
confidence: 92%
“…This result was in accordance with several in vitro studies, indicating THP-1-derived macrophages as a well-characterized model for studying macrophage polarization [16,17,2325]. …”
Section: Resultssupporting
confidence: 92%
“…In accordance with previously published data (31), this showed that CCL18 was selectively induced in M2 cells (Supplemental Figure 1A). In M0 ( Figure 3A) and M2 (Supplemental Figure 2B) cells, 0.5 g/mL (but not 0.05 g/mL), recombinant CCL18 induced an increase in previously reported response genes including CCL2 and CCL3, an effect that was not observed in M1 cells (Supplemental Figure 2A).…”
Section: Functional Studies Of Ccl18 In Human Macrophages and Adipocytessupporting
confidence: 93%
“…18 THP-1 macrophages transduced with versikine-plasmid or empty-vector control were cocultured with human myeloma MM1.S cells for 48 hours and RNA-seq analysis was performed on each cell type. Remarkably, only 23 genes were differentially expressed in MM1.S cells exposed to versikine-secreting macrophages and all were upregulated: among these, 13 genes defined a type I interferon (IFN) signature ( Figure 1H).…”
Section: Resultsmentioning
confidence: 99%